2021
DOI: 10.1002/cac2.12164
|View full text |Cite
|
Sign up to set email alerts
|

YB1 regulates miR‐205/200b‐ZEB1 axis by inhibiting microRNA maturation in hepatocellular carcinoma

Abstract: Background: Y-box binding protein 1 (YB1 or YBX1) plays a critical role in tumorigenesis and cancer progression. However, whether YB1 affects malignant transformation by modulating non-coding RNAs remains largely unknown. This study aimed to investigate the relationship between YB1 and microRNAs and reveal the underlying mechanism by which YB1 impacts on tumor malignancy via miRNAs-mediated regulatory network. Methods:The biological functions of YB1 in hepatocellular carcinoma (HCC) cells were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…YBX1 was also found to be upregulated in HCC and was negatively associated with the overall survival in our analysis. Other studies confirmed the proposed oncogenic effect of YBX1 in HCC [ 48 , 77 , 78 ]. YBX1 has a wide variety of functions and acts also as RBP and influences RNA stability, splicing and translation [ 65 ].…”
Section: Discussionsupporting
confidence: 61%
“…YBX1 was also found to be upregulated in HCC and was negatively associated with the overall survival in our analysis. Other studies confirmed the proposed oncogenic effect of YBX1 in HCC [ 48 , 77 , 78 ]. YBX1 has a wide variety of functions and acts also as RBP and influences RNA stability, splicing and translation [ 65 ].…”
Section: Discussionsupporting
confidence: 61%
“…An increasing number of studies have demonstrated that non-m 6 A RNA modification regulators are significantly correlated with MES transition. It has been reported that ADAR and YBX1 promote MES transition by regulating oncogenic microRNA maturation ( 65 , 66 ). Nevertheless, research on RNA modifications beyond m 6 A is still not as mature as that for m 6 A for many reasons, including technology limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This protein is also found in mRNP complexes and may play a role in microRNA processing. The possibility of YBX1-binding to multiple motifs distributed across the mRNA coding Spike could reduce cytoplasmic protein availability [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%